Increased glycodelin levels in gynecological malignancies. Issue 3 (1st May 2001) - Horowitz, I. R.; Cho, C.; Song, M.; Flowers, L. C.; Santanam, N.; Parthasarathy, S.; Ramachandran, S.
Abstract : Glycodelin, an immunosuppressive protein with contraceptive properties, is synthesized by a variety of tissues and cell types. The ability of reproductive tissues to synthesize glycodelin is of major interest in pregnancy and disease conditions. We studied glycodelin levels in subjects with malignant gynecological tumors and in control subjects. Using a polyclonal glycodelin antibody against the synthetic glycodelin peptide sequence, an enzyme-linked immunosorbent assay (ELISA) was devised to measure plasma glycodelin levels. The assay detected as much as 5 ng/ml of glycodelin. There was a significant increase in plasma glycodelin levels in endometrial > ovarian > cervical cancer subjects when compared to those of controls. Strong expression of mRNA and protein were found in the ovarian and endometrial tumor tissues. Given glycodelin's immunosuppressive abilities, increased level of glycodelin may facilitate tumor growth in gynecological malignancies.